Desire Work : Ex-Gay and Pentecostal Masculinity in South Africa - Hackman, Melissa, 1978- (Book collections on Project MUSE., 2018)
In postapartheid Cape Town -- Africa's gay capital -- many Pentecostal men turned to "ex-gay" ministries in hopes of "curing" their homosexuality in order to conform to conservative Christian values and African social norms. In this book the author traces the experiences of predominantly white ex-gay men as they attempt to forge a heterosexual masculinity and enter into heterosexual marriage through emotional, bodily, and religious work. These men subjected themselves to daily self-surveillance and followed prescribed behaviors such as changing how they talked and walked. Ex-gay men also saw themselves as participating in the redemption of the nation, because South African society was perceived as suffering from a crisis of masculinity in which the country lacked enough moral heterosexual men. By tying the experience of ex-gay men tot he convergence of social movements and public debates surrounding race, violence, religion, and masculinity in South Africa, the author offers insights into the construction of personal identities in the context of sexuality and spirituality